2021
DOI: 10.15835/nbha49111786
|View full text |Cite
|
Sign up to set email alerts
|

Zoophagous entomofauna and entomopathogenic agents reported on Cydalima perspectalis (Walker, 1859) in north-western of Romania

Abstract: In Europe, the box tree moth, Cydalima perspectalis (Walker, 1859) was first reported in 2006, in southwestern Germany, then spread to almost all countries. Larvae of this species affect the aesthetic value of the box tree. In the last period, numerous studies were carried out regarding the identification of useful entomofauna that reduce the numerical density of the population of Cydalima perspectalis. In this study conducted in north-western Romania (Cluj County, in 2019), entomopathogens and useful entomofa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Harizanova et al (2018) monitored bacterial entomopathogen flora in C. perspectalis populations and found an average contamination of 10.2% with Bacillus anaericanus and 52.4% with Bacillus popilliae. In a similar study, Hulujan et al (2021) found that most larvae have been infected with Bacillus species. Moreover, Bacillus thuringiensis was isolated from C. perspectalis larvae in natural populations, and 85% mortality was obtained with this isolate in bioassay trials (Usta 2022).…”
Section: Bacterial Entomopathogensmentioning
confidence: 83%
“…Harizanova et al (2018) monitored bacterial entomopathogen flora in C. perspectalis populations and found an average contamination of 10.2% with Bacillus anaericanus and 52.4% with Bacillus popilliae. In a similar study, Hulujan et al (2021) found that most larvae have been infected with Bacillus species. Moreover, Bacillus thuringiensis was isolated from C. perspectalis larvae in natural populations, and 85% mortality was obtained with this isolate in bioassay trials (Usta 2022).…”
Section: Bacterial Entomopathogensmentioning
confidence: 83%
“…It has also been recently detected in France [50], Iran [51] and other regions of Spain (personal communication). Occasionally, another dipteran species, Exorista larvarum (L.), is reported in Romania as C. perspectalis [52], but Martini et al [53] indicated that C. perspectalis is not a suitable host for this parasitoid. Although the most recent works on C. concinnata are related to the introduction of the parasitoid for the control of Lymantria dispar (L., 1778) in the United States, the species is native to Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010 the pest has spread throughout the country. Hulujan et al (2021) in a study conducted in western Romania, on the natural enemies, found that pupae of the box tree moth had a parasitism rate between 9.2 and 18.8% and a predation frequency between 12.5 and 19%. The earwig Forficula auricularia L. was observed feeding on moth pupae.…”
mentioning
confidence: 99%